Special children in the custody dispute: the hidden voice - Mobarak Ali, Bashiran Begum (IIUM Press, 2009)
Special or disabled children are born with disabilities, whether they be mental and/or physical disabilities. There are cases where a person becomes disabled after an accident or a disease at a later point of life. Generally, in custody disputes or child maintenance questions, there are no extra provisions for affected disabled children, even though disabled children have been given special recognition by the United Nations. This paper aims to explore the fate of disabled children in our era of globalization, and to determine whether Malaysians law can provide justice to these children. It will study and discuss the relevant laws hat deal with the rights of special children in custody disputes and questions of maintenance.